2022
DOI: 10.3389/fphys.2022.827435
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular and Developmental Roles of Cullins, Neddylation, and the COP9 Signalosome in Dictyostelium discoideum

Abstract: “Cullins (CULs) are a core components” of cullin-RING E3 ubiquitin ligases (CRLs), which regulate the degradation, function, and subcellular trafficking of proteins. CULs are post-translationally regulated through neddylation, a process that conjugates the ubiquitin-like modifier protein neural precursor cell expressed developmentally downregulated protein 8 (NEDD8) to target cullins, as well as non-cullin proteins. Counteracting neddylation is the deneddylase, COP9 signalosome (CSN), which removes NEDD8 from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 169 publications
(262 reference statements)
0
5
0
Order By: Relevance
“…Herein, we detected 9 genes of the cullin family of proteins. Cullin proteins were also detected in Dictyostelium ( Kim et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Herein, we detected 9 genes of the cullin family of proteins. Cullin proteins were also detected in Dictyostelium ( Kim et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…COP9 signalosome (CSN) and NEDD8 protease 1 (NEDP1), which release substrates and NEDD8 (Fig. 2 ) [ 123 , 124 ]. In 2022, A study demonstrated that PML/RARα fusion proteins that drive chromosomal translocation production in acute promyelocytic leukemia (APL) are assembled by LLPS into nucleosomal structures.…”
Section: Ptms Of Proteins Related To Eukaryotic Phase Separationmentioning
confidence: 99%
“…The CSN signalosome complex supports numerous developmental events in eukaryotes, partly by facilitating ubiquitin-dependent degradation of aged, misfolded, and mislocalized proteins and promoting ubiquitin homeostasis (Kim et al, 2022). For example, studies have shown that selected subunits of the CSN complex directly interact with the 19S regulatory unit of the 26S proteasome complex in plants and animals (Yu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%